AKTIVITAS ANTIBAKTERI EKSTRAK ISOLAT FUNGI ENDOFIT DARI AKAR MANGROVE (Rhizophora apiculata Blume) SECARA KLT BIOAUTOGRAFI - Fitriana Fitriana; Eka Nurshitya (Fakultas Farmasi UMI, 2017)
Endophytic fungi have the ability to produce bioactive compounds one of which is antibacterial. A search of bioactive compounds in this research are the first was isolated endophytic fungi on the roots of mangrove then be purified and macroscopic order to obtain pure 6 isolates endophytic fungi. Proceed with the screening test to test bacteria and endophytic fungal isolates obtained first by IJM 2 code which provides activity against 5 test bacteria with the formation of the largest inhibition zone diameter. Then proceed with the fermentation of isolates IJM 2 for 21 days at room temperature using Potato Dextrose Broth medium after the separation to obtain a supernatant and mycelia. Then proceed with the solvent extraction using ethyl acetate and the extract obtained extract supernatant and mycelia. The extract obtained is then followed by TLC-Bioautografi testing using the eluent n-butanol: acetic acid: water (8: 1: 2). Results chromatogram profile with KLT-Bioutografi method showed antibacterial activity against bacteria Shigella dysentriae, Pseudomonas aeruginosa, Salmonella thypii, Vibrio cholerae, Stahpylococcus aureus.